The Global Impact of the COVID-19 Pandemic on Individuals' and Couples' Sexuality - Eleuteri, Stefano; Alessi, Federica; Petruccelli, Filippo; Saladino, Valeria (Frontiers in Psychology, 2022)
COVID-19 pandemic and its related restrictions significantly impacted individuals’ health, well-being and security. Isolation, limitation of movement, social distancing, and forced cohabiting have had a strong influence on all areas of people’s lives as well as on their sexuality. Investigating how COVID-19 outbreak and its consequences impacted people’s sexuality is the primary aim of this review. Particularly, we focused on: (1) the variables associated with the improvement or the deterioration of individuals’ and couples’ lives during pandemic; (2) the use of sex as a coping strategy; (3) the impact of COVID-19 outbreak on LGB people. Results have shown that the worsening of sexual life seems to be related to couples’ conflict, emotions and psychological difficulties, being female, being single or away from the partner, being an health care worker and having children. Moreover, a detrimental effect on sexuality was associated to stress, forced cohabitation, routine, anxiety and worry about the job and the pandemic, feeling partner distance, being unhappy with their partner and lack of privacy. On the other hand, improvements in sexuality were associated with living happy times with the partner, being happy and satisfied with the partner, feeling less stressed and more bored, having more free time, having less recreation opportunities and having minor workload. During the pandemic was found an increase in using sex toys, pornography consumption, masturbating and in tryng sexual experimentations. Among LGB people, it was found an increase in the number of casual sexual partners maybe due by the perceived lower likelihood of transmission through sex. Moreover, the increase in sexual activity may have represent a coping strategy to face with the quarantine-related distress.